Associations Between Intravenous Iron, Inflammation and FGF23 in Non-Dialysis Patients with Chronic Kidney Disease Stages 3-5 - Katarzyna Muras-Szwedziak; Michal Nowicki (Karger Publishers, 2018)
Background/Aims: Both iron deficiency and chronic inflammation are highly prevalent in patients with chronic kidney disease (CKD). The effect of intravenous iron infusion on mineral metabolism in CKD may be modified by inflammation. Intravenous iron theraphy may reduce peripheral degradation, secretion, clearence of iFGF23 and lead to hypophosphatemia. The aim of the study was to evaluate the effect of intravenous iron on mineral metabolism in CKD patients. Methods: 35 non-dialysis patients with CKD stages 3-5. received 100 mg/24h of ferric oxide saccharated solution for 5 days. Serum calcium (Ca), phosphorus (P), parathormone (PTH), intact-FGF23 (iFGF23), C-terminal-FGF23 (cFGF23), bone alkaline phosphatase (BAP) and high-sensitive CRP were assessed on day 1 and 3 at baseline and 2 hours after each dose administration and once on day 6. Plasma iFGF23 and cFGF23, as well as serum BAP were measured with ELISA and other parameters with standard automated laboratory methods. Results: Serum iFGF23 increased after iv iron on day 1 and 6 (from 268.9±446.5 to 326.3±529.9 on day 1; p=0.05 and to 451.4±601 pg/mL on day 6; p=0.03). cFGF23 was reduced only on day 1 (from 654.3±441.3 to 473.6±414 RU/mL; p=0.016). P concentration decreased significantly two hours after the first iron infusion (from 1.69±0.5 to 1.54±0.35 mmol/l; p=0.003). In following days the changes of cFGF23, P and of other calcium-phosphate metabolism were not significant. Serum CRP correlated neither with iFGF-23 nor cFGF-23. Conclusion: Intravenous iron supplementation may only transiently affect the production and degradation of FGF23 resulting in hypophosphatemia at the commencement of iron therapy. Chronic low-grade inflammation does not seem to play a role in that mechanism.